Computer aided systems theory -- EUROCAST 2015 : 15th International Conference, Las Palmas de Gran Canaria, Spain, February 8-13, 2015, Revised selected papers /: 15th International Conference, Las Palmas de Gran Canaria, Spain, February 8-13, 2015, Revised selected papers. (2015) - Unknown
No abstract available